Role of “Compartment Pressure” Measurement in Extensive Burns of Extremities - R. P. Sahi; N. N. Mahendra; S. K. Bhatnagar; S. B. Gupta (Indian Journal of Plastic Surgery)
The rise in “compartment pressure”, following deep or circumferential burns of extremities, leads to production of “compartment syndrome”. The resultant reduction of perfusion pressure causes ischaemic necrosis of unburnt deeper tissues in the limbs. This can be prevented by accurate measurement of “compartment pressure” for which needle infusion technique has been used in this study. The procedure was found to be simple, cheap and reliable . To prevent ischaemic tissue necrosis the measurement of “compartment pressure” should be added to the list of parameters used for evaluating patients with thermal injury of the limbs.